Do Chinese firms incur a liability of localness as a result of inward foreign direct investment? Local firms’ perspective - Jiang, Fuming; Stening, B. (ANZIBA, 2012)
Liability of foreignness has been one of the building blocks of theories of multinational enterprises. This paper looks at a parallel issue - the liability of localness that local firms may face as a result of foreign firms’ presence in their country. The results show that while local Chinese firms enjoy superior location based advantages over their foreign counterparts and these, together with their firm-specific advantages, have a significant positive effect on their performance, foreign firms’ superior firm-specific and multinationality advantages appear to erase the magnitude of such effects and create a significant negative impact on local Chinese firms’ performance. This suggests that local Chinese firms incur a liability of localness at home in relation to the presence of foreign firms in the country.